PENDIDIKAN PENULIS DAN PENGGUNAAN LITERATUR PADA ARTIKEL BERKALA ILMU PERPUSTAKAAN DAN INFORMASI: SEBUAH KAJIAN BIBLIOMETRI - Pergola Irianti (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
This study sought to determine (1) the characteristics of the referenced literature, (2) the use of literature by authors based on their education levels, (3) the percentage of individual and group authorship based on authors’ education levels in articles published in Berkala Ilmu Perpustakaan dan Informasi (BIPI) during the period of 2011-2015. As a description quantitative study, data was collected through documentation method. Analysis units of this study were all articles published in the journal during the period. Data was analysed by using percentage formula and listed in frequency tables using MS Excel. Results showed that during the last five years BIPI has published 45 articles written by 48 authors. Book reference (79,19%) was higher than the journal reference (15,45%.) The use of articles written in Indonesian language was also higher than the the use of articles written in foreign languages. It was also found that the literature was 1-10 years old of novelty. There was no significant difference of the percentage of the cited reference type, the language of instruction, and the age of among authors based on their education levels. Both individual and group athorship showed no significant difference based on authors’ education levels.